Pengaruh Model Inquiry Based Learning terhadap Hasil Belajar Fisika Siswa Madrasah Aliyah Negeri 3 Medan - Syahdina Elbi; Khairiah Khairiah; Rita Destini; Rofiqoh Hasan Harahap (Departement of Mathematics Education, 2024)
The objective of this research was to determine the effect of inquiry-based learning models on students' physics learning outcomes. This research uses a type of quasi-experimental research by taking the subject of rotational dynamics and rigid body equilibrium. Samples were taken using random sampling techniques which obtained class XI MIPA 2 as an experimental class and class MIPA 1 as a control class. Data collection for learning outcomes data was carried out with a multiple-choice test technique of 30 questions. Data analysis using objective learning outcomes test instruments obtained with an experimental class average of 21.68 and a control class average of 18.17, with an experimental class standard deviation of 4.54 and a control class standard deviation of 6.16 (significant < 0.05). With a significance of less than 0.05, this shows that there was an influence on the experimental class and the control class on, so it can be concluded that the application of the Inquiry Based Learning model has an influence on the physical learning outcomes of students